Health related quality of life and psychological parameters in different polycystic ovary syndrome phenotypes: a comparative cross-sectional study - Bahadori Fatemeh; Jahanian Sadatmahalleh Shahideh; Mirzaei Negin (BMC, 2021)
Abstract Background Polycystic Ovary Syndrome (PCOS) is associated with high levels of phsychological implications and detriments to Quality of Life (QoL). The aim of this study was to assess Health- Related Quality of Life (HRQoL), depression, and anxiety in Iranian women with different PCOS phenotypes. Methods The present observational, cross-sectional study was carried out on 239 PCOS women who were classified on the basis of Rotterdam criteria into four categories: A (n = 77), B (n = 38), C (n = 68), and D (n = 56). They asked to fill out three questionnaires, namely, HRQoL, SF-12, and HADS. Results No significant differences were observed between the four PCOS phenotypes for anxiety, depression and QoL, as well as HRQoL domains related to infertiliy, weight and emotional problems (P > 0.05). Phenotypes A and B had worse HRQoL related to hirsutism (13.98 ± 5.22, 14.13 ± 6.23, P < 0.001). In addition, no significant differences were observed between them for HRQoL domains. While the score of acne in phenotype D (19.60 ± 5.12, P = 0.003) and menstrual score in phenotype C were significantly higher comparing to the other PCOS groups (16.82 ± 3.87, P < 0.001). Conclusion Presenting similar psychological profiles in all phenotypes unveils the importance of pychological well-being screening, even in milder reproductive phenotypes.